Психологічна структура особистості поліцейських в контексті професійної здійсненності - Пономаренко, Я. С.; Ponomarenko, Ya. S.; Пономаренко (Посохова) Яна Сергіївна (Габітус. - 2022. - Вип. 36. - С. 283-288, 2022)
Висвітлено факторну структуру особистості та ключові показники готовності до змін у практиці поліціювання. Виявлено взаємозв’язки структурних факторів особистості та показників особистісної готовності до змін у поліцейських з різним рівнем професійного самоздійснення.

The article presents theoretical research on the structure of personality and its readiness for change. The factor structure of the personality and key indicators of readiness for changes in policing practice are highlighted. The purpose of the study is to identify the relationship between structural factors of personality and indicators of personal readiness for change in police officers who have different levels of professional self-fulfillment (PS). The sample of the study consisted of 62 police officers. With the use of the «Questionnaire of professional self-fulfillment» by O. Kokun and using the method of clustering according to the principle of k – means, we formed three groups of subjects: low, medium and high levels of PS.. The first group (with a low level) consisted of 28 subjects, the second group (with a high level) included 33 subjects. 24 respondents with an average level were excluded from further research. The study used the “Five-Factor Personality Questionnaire” (Big Five) by R. McCrae and P. Costa and the method «Personal Readiness for Change» by A. Rolnic, S. Heather, М. Gold, С. Hull in the adaptation by N. Bazhanova. It has been empirically established that there are four negative and two positive connections in the group of low-level police officers. This shows that in the first group, the increase in openness and friendliness is accompanied by a decrease in creativity, adaptability, self-confidence and productivity. Six positive and two negative connections were diagnosed in a group of highlevel police officers. Thus, in the second group, the increase in extraversion coincides with an increase in self-confidence and professional success. However, an increase in openness to contacts is accompanied by a decrease in selfconfidence and an increase in adaptive abilities and tolerance for ambiguity. Police officers with a high level of PS with increased perseverance and sincerity in the performance of official duties have an increase in readiness to adequately accept uncertain situations, which significantly affects their effectiveness as a specialist

Отражена факторная структура личности и ключевые показатели готовности к изменениям в практике полицейского. Выявлены взаимосвязи структурных факторов личности и показателей личностной готовности к изменениям у полицейских с разным уровнем профессионального самоосуществления.
Psychological structure of police officers personality in the context of professional self-fulfillment
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Юридична психологія. Legal psychology. Юридическая психология; поліцейські; police officers; полицейские; особистість; personality; личность; професійне самоздійснення; professional self-realization; профессиональное самоосуществление; готовність до змін; readiness for change; готовность к переменам; поліціювання; policing